LEVEL OF VOCAL SINGING PERFORMANCE OF SPECIALIZED SCHOOL STUDENTS WITH DISABILITIES - Safarova Dilsora Sheraliyevna; Yuldoshev Umidjon Yuldoshevich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article is about raising the level of vocal performance of special school students with disabilities, especially children with such disabilities are known to be more talented than others. Such students' perfect interpretation of the sound, determining its musical pitch, connecting it with practical reality, and singing with the help of voice through superficial and external feeling determines the level of their performance level, and this article allows to solve such issues.